Cation-Mediated Acid-Base Pairs for Mild Oxidative Cleavage of Lignocellulosic β-1,4-Glycosidic Bonds - Hongguang Zhang; Aiguo Wang; Ruixuan Zhao; Jinguang Hu (BioResources, 2024)
Solar-driven lignocellulosic biomass photoreforming holds significant promise for the production of value-added chemicals and fuels. The cleavage of the β-1,4-glycosidic bond is crucial for the effective conversion of lignocellulosic biomass. Polymeric carbon nitride (PCN) with acid-base pairs (M-C sites) is developed through heteroatomic carbon incorporation and cation insertion. It can be used for the gentle oxidation of cellobiose to monosaccharides, bypassing the formation of organic acids such as gluconic acid and glucaric acid. A series of different alkaline/alkaline-earth cation for regulation of acid-base pairs exhibited a negative correlation between β-1,4-glycosidic bond cleavage and cation radii. In particular, the introduction of short-radius cations (such as Li) into PCN enabled the formation of acid-base (M-C) pairs characterized by strong acidity. It also enhanced electron delocalization around M-C sites, potentially promoting the generation of reactive radicals in the reaction. Electron paramagnetic resonance analysis confirmed the presence of •OH radicals. The mild oxidative species, are the primary reactive radicals responsible for β-1,4-glycosidic bond cleavage in cellobiose. This study provides insightful evidence for the rational regulation of acid-base sites in facilitating β-1,4-glycosidic bond cleavage. It sheds light on the oxidative cleavage mechanisms integral to lignocellulosic biomass photoreforming, offering insights for advancing sustainable biomass conversion technologies.